Methods of Creed and Moral Education: An Analysis of Ibn Miskawaih and Imam Al-Ghazali in Shaping the Religious Character of MAN 1 Sragen Students - Janarko; Usman Abu Bakar; A. Mufrod Teguh Mulyo (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to examine the Aqidah and Akhlaq education method of analysis by Ibn Miskawaih and Imam Al-Ghazali in shaping the religious character of students at MAN 1 Sragen in the 2024/2025 academic year. This study is motivated by the importance of religious values education in shaping the character of the young generation who have noble morals and are based on Islamic teachings. This study formulates three main focuses of the Aqidah and Moral Education Method, Analysis by Ibn Miskawaih and Imam Al-Ghazali in Shaping the Religious Character of Students at MAN 1 Sragen (2024/2025 Academic Year). The approach used was qualitative, using field research. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using a descriptive-critical approach, referring to the moral and character education theories of Imam Al-Ghazali and Ibn Miskawaih, which emphasize the habituation of good deeds, control of desires, and the role of educators as spiritual and moral guides. The results of the study indicate that the Aqidah Akhlak education method at MAN 1 Sragen is systematically structured through the integration of Islamic values into the curriculum and habituation activities. The learning methods used are participatory and contextual, such as value discussions, case studies, and teacher role models. This method has proven effective in shaping students' religious character, marked by increased spiritual awareness, social concern, and behavior that reflects noble morals. This aligns with the views of Al-Ghazali and Ibn Miskawaih that moral education is not merely the transmission of knowledge, but a continuous process of soul formation.